Investigasi Determinan Sosioekonomi pada Perempuan dengan Rumah Tangga Patriarki - Rafa Fayza Afrizal; Friska Aulia Dewi Andini; Salsabila Yori Harmen (Universitas Pendidikan Ganesha, 2025)
The persistence of patriarchal structures within households limits women’s opportunities and hinders gender equality. Living in households with a patriarchal culture poses several challenges for women, such as restricted access to education and healthcare, limited economic opportunities, and exposure to violence. This research investigates the socioeconomic determinants that influence the likelihood of women residing in patriarchal households in Indonesia. This study used cross-sectional data from the Indonesia Demographic and Health Survey (IDHS) for 2007, 2012, and 2017. We constructed the patriarchy index as the dependent variable to estimate the likelihood of women residing in patriarchal households and employed logistic regression analysis. The findings revealed that there is a negative and significant relationship between women’s years of schooling and the probability of women being in a patriarchal household (p<0.01). Women with richer and richest wealth index households also have a lower probability of being in a patriarchal household (p<0.01). Meanwhile, women who live in rural, a large number of children, and those with lower socioeconomic status are more likely to be in patriarchal households (p<0.01). This study emphasized the significant role of education concerning the likelihood of women being in patriarchal households. It also highlighted that women residing in rural areas are more likely to be in patriarchal households due to social isolation and limited access to education and healthcare. The results demand policy interventions to promote gender equality, particularly in increasing women's access to education and healthcare, including targeted rural development programs.